2020
DOI: 10.1167/tvst.9.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Noncontact Sequential Imaging of the Iridocorneal Angle and the Cornea of the Eye

Abstract: High-resolution imaging of the critical anatomic structures of the eye, especially of the anterior chamber, in vivo, remains a challenge, even with currently available state-of-the-art medical imaging techniques. This study aims for the noninvasive and noncontact sequential imaging of the iridocorneal angle, especially the trabecular meshwork (TM) and the cornea of the eye in high-resolution using a newly developed imaging platform. Methods: Bessel beam scanned light sheet fluorescence microscopy is used to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…They only reported images in ex vivo porcine eyes and reported many user difficulties. Hong et al reported a prototype system also implementing an axicon lens to generate Bessel beam illumination in a light sheet fluorescence microscopy (LSFM) scheme (60,61). This resulted in a more accessible system with a long working-distance objective, to impart a noncontact nature to image acquisition.…”
Section: Bessel Beam/axicon Assistedmentioning
confidence: 99%
“…They only reported images in ex vivo porcine eyes and reported many user difficulties. Hong et al reported a prototype system also implementing an axicon lens to generate Bessel beam illumination in a light sheet fluorescence microscopy (LSFM) scheme (60,61). This resulted in a more accessible system with a long working-distance objective, to impart a noncontact nature to image acquisition.…”
Section: Bessel Beam/axicon Assistedmentioning
confidence: 99%
“…nal-to-noise ratio, reduced scattering and shadowing artefacts, and higher axial res The self-reconstruction property of the Bessel beam was instrumental in increasing t trast in the scattering environment. They later reported a sequential imaging system high-resolution imaging of the ICA and the cornea of the eye and demonstrated imaging in New Zealand white rabbits [55,72]. Figure 5 shows the reported sequen aging system utilizing Bessel beam-based LSFM for TM imaging [72].…”
Section: Bessel Beam-based Light Sheet Fluorescence Microscopy (Lsfm)...mentioning
confidence: 99%
“…They later reported a sequential imaging system high-resolution imaging of the ICA and the cornea of the eye and demonstrated imaging in New Zealand white rabbits [55,72]. Figure 5 shows the reported sequen aging system utilizing Bessel beam-based LSFM for TM imaging [72]. Suchand Sandeep et al reported the three-dimensional (3D) visualization of the TM on an intact ex vivo porcine eye utilizing a modified version of the Bessel beam-based system [59].…”
Section: Bessel Beam-based Light Sheet Fluorescence Microscopy (Lsfm)...mentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging of the retinal layers using the advanced techniques is challenging due to the non-availability of the sophisticated non-invasive system where the retinal size animal models is ten-fold smaller than that of humans. Also, there are very limited in vivo ocular non-invasive imaging methods available for retinopathy with in depth resolution [102][103][104][105][106][107]. Recently, an early detection of DR using a non-mydriatic, full field electroretinopathy, easy to operate devise was reported.…”
Section: Imaging Biomarkersmentioning
confidence: 99%